Obesity affects graft function but not graft loss in kidney transplant recipients. Issue 1 (January 2020) - Bellini, Maria Irene; Koutroutsos, Kostas; Nananpragasam, Hannah; Deurloo, Emily; Galliford, Jack; Herbert, Paul Elliot
Objective: This study was performed to examine the suitability of transplantation in kidney transplant recipients (KTRs) with a high body mass index (BMI). Methods: In total, 370 consecutive KTRs stratified according to the World Health Organization BMI categories were retrospectively analysed. The estimated glomerular filtration rate (eGFR) was used to assess allograft function. Results: The mean BMI was 26.2 kg/m 2 . Among all patients, 148 (40.0%) were pre-obese, 47 (12.7%) were class I obese, 11 (3.0%) were class II obese, and 9 (2.4%) were class III obese. A linear trend for male sex and younger age was observed from the normal BMI group through the progressively higher groups. Overweight and obese KTRs had a significantly higher incidence of pre-transplant diabetes, but there was no difference in post-transplant new-onset hyperglycaemia. Obesity was not a significant risk factor for a lower eGFR at the 1-year follow-up, but it became significant at the 2- and 3-year follow-ups. Graft loss occurred in 28 patients, and 25 patients died during follow-up. No difference in all-cause allograft loss was found among the different BMI groups during follow-up. Conclusion: Obesity affects the eGFR in the long term. Allograft survival was lower, but not significantly.